Taking over the World? Automation and Market Power - Richard Haarburger; Henry Stemmler (ZBW - Leibniz Information Centre for Economics, 2023)
This paper studies how automation technology affects market power in the global economy. We develop a theoretical model in which firms' markups are endogenous to factor input choices based on technology levels, but are also affected by technology adoption of other domestic and foreign firms. In an empirical analysis, we find that market power, measured as the markup of price over marginal cost, declines on average with higher levels of automation. However, there is substantial heterogeneity, with firms in the highest revenue and markup quintile gaining market power. Moreover, we find that exposure to foreign automation increases competition in the local market.
Keywords: O33; F41; F12; D43; 330; Automation; Markups; Robots; Market Concentration